Long-term stability of Class II malocclusion treatment with the cantilever bite jumper - Lancia, Melissa; Ciantelli, Thales Lippi; Bellini-Pereira, Silvio; Aliaga-Del Castillo, Aron; Moro, Alexandre; Henriques, José Fernando; Janson, Guilherme (American journal of orthodontics and dentofacial orthopedics, 2022)
This study aimed to assess the long-term stability of Class II malocclusion treatment with the Cantilever Bite Jumper (CBJ) after 13 years of follow-up. The treatment group comprised 10 Class II Division 1 malocclusion patients treated with the CBJ, followed by fixed appliances, analyzed at 3 stages: pretreatment (aged 11.56-14.32 years), posttreatment (aged 16.34-19.58 years), and long-term posttreatment (aged 29.04-32.33 years). The control group included 15 subjects with normal occlusion. Intragroup treatment changes comparison was performed with repeated measures and analysis of variance followed by Tukey tests. Intergroup comparisons regarding the long-term posttreatment changes were performed with t tests. No statistically significant relapse was observed during the follow-up period. Morever, the treated group presented a significantly smaller increase in lower anterior facial height and greater retrusion of the lower lip than the control group in the posttreatment period. Treatment with the CBJ, followed by fixed appliances, is a stable alternative for Class II Division 1 malocclusion correction. The dentoskeletal and soft-tissue changes obtained during treatment remained stable in the long-term posttreatment follow-up. •Long-term stability of Class II malocclusion treatment was assessed.•Evaluations were performed at T1, T2, and after follow-up of 13 years.•Treatment changes remained stable in the long-term posttreatment follow-up.•A normal occlusion group was used to compare the long-term posttreatment changes.•A greater lower lip retrusion was observed in the treated group at long-term.